1997
DOI: 10.1289/ehp.97105712
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced oxidative cellular damage in human fetal lung fibroblasts (MRC-5 cells).

Abstract: Epidemiological evidence suggests that cadmium (Cd) exposure causes pulmonary damage such as emphysema and lung cancer. However, relatively little is known about the mechanisms involved in Cd pulmonary toxicity. In the present study, the effects of Cd exposure on human fetal lung fibroblasts (MRC-5 cells) were evaluated by determination of lipid peroxidation, intra-cellular production of reactive oxygen species (ROS), and changes of mitochondrial membrane potential. A time- and dose-dependent increase of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(44 citation statements)
references
References 27 publications
4
37
1
Order By: Relevance
“…However, at 3 and 6 h, the loss of ⌬ m was indiscernible. Although it has been reported that cadmium was able to cause the loss of ⌬ m via oxidant injury (32,33), no significant increase in intracellular oxidants, such as hydrogen peroxide or superoxide, in the cadmium-treated cells was observed by flow cytometry with dichlorodihydrofluorescein diacetate and dihydroethidium in our study (data not shown).…”
Section: Induction Of Apoptosis By Cadmium-contrasting
confidence: 77%
“…However, at 3 and 6 h, the loss of ⌬ m was indiscernible. Although it has been reported that cadmium was able to cause the loss of ⌬ m via oxidant injury (32,33), no significant increase in intracellular oxidants, such as hydrogen peroxide or superoxide, in the cadmium-treated cells was observed by flow cytometry with dichlorodihydrofluorescein diacetate and dihydroethidium in our study (data not shown).…”
Section: Induction Of Apoptosis By Cadmium-contrasting
confidence: 77%
“…Cadmium is a potent inducer of MT synthesis that not only acts through metal response elements of the MT gene to up-regulate gene transcription (Karin et al, 1984), but can also cause intracellular free radical generation and lipid peroxidation, DNA damage and a characteristic apoptotic response (El Azzouzi et al, 1994;Yang et al, 1997). Apoptosis induced by cadmium is preceded by the participation of oxidative stress, with up-regulation of oxidant stress genes such as glutathione S-transferase and g-glutamylcysteine synthetase, activation of redox sensitive transcription factor AP-1 and NF-kB, as well as induction of MT-1 and MT-II synthesis (Hart et al, 1999;Zhou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the synthesis of MT was shown to be induced several-fold during oxidative stress (Sato and Bremner, 1993) to protect the cells against cytotoxicity (Aschner et al, 1998) and DNA damage (Cai et al, 1995). In particular, MT synthesis is induced following treatment with cadmium, an environmental pollutant that is able to cause oxidative stress, DNA damage and apoptosis (El Azzouzi et al, 1994;Yang et al, 1997). The protective role of MT may also depend on the nuclear/cytoplasmic localisation of MT in the cell.…”
mentioning
confidence: 99%
“…This finding led Snider et al (55) to conclude that air-space enlargement was due to overdistention of less abnormal air spaces by fibrotic and atelectatic areas. In vitro, cadmium induces oxidative cellular damage, including lipid peroxidation and production of reactive oxygen species in human fetal lung fibroblasts (57), and release of oxidant radicals from guinea pig alveolar macrophages (AMs) (58). Alveolar epithelial type 2 cells develop resistance to oxidant-induced cytotoxicity after repeated exposure to cadmium aerosols (59).…”
Section: Cadmiummentioning
confidence: 99%